2001
DOI: 10.1067/mtc.2001.112469
|View full text |Cite
|
Sign up to set email alerts
|

Improved results of atherosclerotic arch aneurysm operations with a refined technique

Abstract: Integrated cerebral protective effect of antegrade selective cerebral perfusion and total arch replacement with an aortic arch branched graft could substantially reduce in-hospital mortality and postoperative neurologic dysfunction in patients with atherosclerotic arch aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
120
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(123 citation statements)
references
References 19 publications
1
120
0
2
Order By: Relevance
“…The avoidance of deep hypothermia may be one of the reasons why HCA was not a significant risk factor for mortality and morbidity. As Kazui et al [22] have reported, antegrade cerebral perfusion ensures a safe operation at temperatures of 22 °C.…”
Section: Discussionmentioning
confidence: 99%
“…The avoidance of deep hypothermia may be one of the reasons why HCA was not a significant risk factor for mortality and morbidity. As Kazui et al [22] have reported, antegrade cerebral perfusion ensures a safe operation at temperatures of 22 °C.…”
Section: Discussionmentioning
confidence: 99%
“…51.1). The shortcoming is the necessity of arch-vessel manipulations, such as cannulation or clamping, which might result in cerebral embolization [24,25,29]. However, these should be overcome by sufficient cautions, that is, safe and gentle cannulation into the less atherosclerotic portions of the arch vessels [26,[29][30][31].…”
Section: Selective Cerebral Perfusionmentioning
confidence: 99%
“…Although operative mortality has decreased, operative morbidity is still a matter of concern [1][2][3][4][5]. Stroke is the most severe complication of aortic arch repair [6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…The number of aortic surgeries has recently increased, with improvement of outcome due to the development of operative techniques, adjuncts, and postoperative care [1][2][3][4][5]. Although the mortality rate of aortic arch repair has recently decreased, the occurrence of stroke, the most severe complication of this type of surgery, is still a matter of concern [6][7][8].…”
Section: Introductionmentioning
confidence: 99%